Gambaran Tingkat Kebisingan dan Pengendaliannya pada Pekerja di Area Produksi PT. Karet XYZ Kota Palembang Tahun 2025 - Salsabila Azzahra; Pitri Noviadi; Intan Kumalasari (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Noise is a physical hazard in the work environment that caan reduce hearing loss, especially in the rubber processing industry. The research aims to describe the noise level and control efforts in the production area of PT. Karet XYZ Palembang City in 2025. This study uses a descriptive design with a cross-sectional approach.  Data were collected through direct noise level measurements using sound level meters at wet and dry production areas by taking 8 measurements and questionnaires on 75 selected purposive sampling workers.  Data analysis was carried out univariately. It shows that most of the measurement points have a noise level above the threshold value of 85 dBA in accordance with the Regulation of the Minister of Health of the Republic of Indonesia Number 70 of 2016. The highest values were recorded in the Hummer Mill engine (89,76 dBA) and the Cooling Tunnel (89,70 dBA). All respondents were exposed to noise for ≥8 hours/day. Noise control has been carried out with administrative techniques and the use of personal protective equipment (PPE) but has not been fully effective from the complaints of 7 workers regarding suboptimal protection. The noise level at PT. Karet XYZ and duration of exposure exceeding threshold values that increase the risk to workers health. It is necessary to increase the effectiveness of noise control with a technical, administrative approach and monitoring the optimal use of personal protective equipment (PPE).